A mixed methods approach to understanding engagement and inclusion of minoritized groups in the society of American foresters - Dahl, Jamie, author; Gloeckner, Gene, advisor; Birmingham, Daniel, committee member; Fernández-Giménez, Maria, committee member; Archibeque-Engle, Shannon, committee member (Colorado State University. Libraries, 2022)
People of color, women, and other groups are minoritized in forestry and natural resource professions (Kern et al., 2015; Kuhns et al., 2004; Otero & Brown, 1996; Sharik et al., 2015). Numerous sources share the concern that natural resources fields must begin to reflect the larger demographic makeup of the U.S., or minoritized groups will continue to miss opportunities to influence and lead natural resources decisions (Finney, 2014; Westphal et al., 2022). We need to understand better how current professionals feel engaged and included if we are to bring more people together to understand, enjoy, use, and tend to our forests and natural places. We also need to appreciate how different people connect to the environment and environmental professions. This transformative mixed methods study blends qualitative and quantitative methods to enhance understanding of engagement and inclusion (E&I) of minoritized groups and other members of the Society of American Foresters (SAF). The study took an innovative approach, utilizing environmental justice as a research frame (Schlosberg, 2004; 2007; Schlosberg & Coles, 2016). The survey was sent to all SAF members in 2021 and utilized established engagement and inclusion measures, including perceptions of culture, respect, organizational commitment, sense of belonging, and stereotype threat vulnerability. Additionally, the study asked questions about the pathway of participants to forestry and natural resources as a focus of study and career. Statistically significant differences were found when comparing groups on these E&I measures. Women had significant differences compared to men, with women having lower perceptions of culture, varied perceptions of respect, lower sense of belonging, lower organizational commitment, and greater perceptions of stereotype threat. Members of color had some significant differences compared to White members, with lower perceptions of SAF culture at the national level; and greater perceptions of stereotype threat and specific career barriers. LGBQ+ members had significant differences compared to non-LGBQ+, including lower culture perception and lower sense of belonging. Age group comparisons also showed significant differences and contributed to predictive associations. Additional statistically significant interactions and predictive associations were also found. Respondents shared their pathways to forestry and NR as a focus of study and career, including information about exposure to nature-based activities as a youth and perceptions of career barriers. Several open-ended questions provided rich qualitative data. These data were analyzed using content analysis and an environmental justice frame. Patterns arose that help explain and enhance our statistical findings and further contribute to established literature. Responding SAF members mentioned fundamental environmental justice (EJ) principles including recognition of philosophies, promotion of capabilities, and participation and inclusion. Some members also commented on the ripple effect that SAF E&I problems could have on various human stakeholders, the natural resource itself, and our world (Schlosberg, 2004; 2007; Schlosberg & Coles, 2016; Schlosberg, 2013). Participants expressed concern for impacts on their fellow SAF members and concern for SAF's sustainability as an organization if diversity, equity, and inclusion (DEI) issues were not addressed better. This research helps convey the urgency and need to keep environmental justice and DEI at the forefront of SAF's evolving strategy and vision. SAF members in this study ask the organization to be a leader in DEI.
Keywords: forestry; minoritized; natural resource; inclusion; engagement; mixed methods